HUBUNGAN MARAH DENGAN KESEHATAN MENTAL DALAM PERSPEKTIF HADIS: (STUDI KASUS MAHASISWA ILMU HADIS UIN SUMATERA UTARA) - Nasution, Lanni Ari; Damanik, Nurliana (IAIN PONOROGO, 2025)
Uncontrolled anger has a negative impact on mental health and reduce one's quality of life. Students, in particular, often face academic and social pressures that can trigger these emotions. In Islamic teachings, the hadith provides valuable guidance in managing emotions so as not to harm oneself or others. This study aims to investigate the relationship between anger and mental health from the perspective of the hadith teachings, focusing on students of the Hadith Study Program at the State Islamic University of North Sumatra. This study uses a qualitative approach with a case study method, where data are obtained through in-depth interviews and observations of five students who have a basic understanding of the hadith. The results of the study indicate that the hadith teachings on anger control, if understood and applied consistently, can reduce the negative impacts of these emotions such as stress, anxiety, and depression, and also improve students' mental well-being and social relations. The conclusion of this study underlines the importance of integrating the hadith teachings in character education and the development of emotional literacy among students. The practical implications are that the results of this study can be used as a reference in designing religious-based counseling guidance programs on campus, as well as encouraging the formation of educational policies that support mental health through an Islamic spiritual approach.